MXenes as a versatile platform for reactive surface modification and superior sodium‐ion storages - Jinjin Wang; Cheng‐Feng Du; Yaqing Xue; Xianyi Tan; Jinzhao Kang; Yan Gao; Hong Yu; Qingyu Yan (Exploration, 2021)
Abstract Owing to the large surface area and adjustable surface properties, the two‐dimensional (2D) MXenes have revealed the great potential in constructing hybrid materials and for Na‐ion storage (SIS). In particular, the facilitated Na‐ion adsorption, intercalation, and migration on MXenes can be achieved by surface modification. Herein, a new surface modification strategy on MXenes, namely, the reactive surface modification (RSM), is focused and illustrated, while the recent advances in the research of SIS performance based on MXenes and their derivatives obtained from the RSM process are briefly summarized as well. In the second section, the intrinsic surface chemistries of MXenes and their surface‐related physicochemical properties are first summarized. Meanwhile, the close relationship between the surface characters and the Na‐ion adsorption, intercalation, and migration on MXenes is emphasized. Following the SIS properties of MXenes, the surface‐induced SIS property variations, and the SIS performance of RSM MXene‐based hybrids are discussed progressively. Finally, the existing challenges and prospects on the RSM MXene‐based hybrids for SIS are proposed.